A structure excited by a DC motor of limited power supply and controlled by a pendulum like device - Brasil, R. M L R F; Balthazar, José Manoel [UNESP]; Feitosa, L. C. (ASME International, 2008)
In this paper, a mathematical model is derived via Lagrange's Equation for a shear building structure that acts as a foundation of a non-ideal direct current electric motor, controlled by a mass loose inside a circular carving. Non-ideal sources of vibrations of structures are those whose characteristics are coupled to the motion of the structure, not being a function of time only as in the ideal case. Thus, in this case, an additional equation of motion is written, related to the motor rotation, coupled to the equation describing the horizontal motion of the shear building. This kind of problem can lead to the so-called Sommerfeld effect: steady state frequencies of the motor will usually increase as more power (voltage) is given to it in a step-by-step fashion. When a resonance condition with the structure is reached, the better part of this energy is consumed to generate large amplitude vibrations of the foundation without sensible change of the motor frequency as before. If additional increase steps in voltage are made, one may reach a situation where the rotor will jump to higher rotation regimes, no steady states being stable in between. As a device of passive control of both large amplitude vibrations and the Sommerfeld effect, a scheme is proposed using a point mass free to bounce back and forth inside a circular carving in the suspended mass of the structure. Numerical simulations of the model are also presented Copyright © 2007 by ASME.
Keywords: Direct current (dc); Equation of motion; Function of time; horizontal motions; In between; international conferences; International designs; Lagrange's equations; large amplitude vibrations; Limited power supply; Motor rotation; Multi-body system (MBS); Non ideal sources; Non-linear dynamics; Numerical simulations; Passive control; point masses; resonance conditions; shear buildings; Sommerfeld effect; Steady states; Step-by-step; Suspended mass; Technical conferences; Architectural design; Computer control; Computer networks; Computer simulation; Computers; Control systems; DC motors; Dynamical systems; Dynamics; Electric machinery; Electric motors; Electric potential; Electroacupuncture; Engineering; Equations of motion; Foundations; Function evaluation; Functions; Information systems; Lattice vibrations; Lead; Machine design; Mathematical models; Mechanics; Motors; Nonlinear programming; Passive networks; Photoacoustic effect; Rotation; Shearing machines; Structural analysis; Technology; Vibrations (mechanical); Vibrators; Structural design